2021
DOI: 10.1088/1755-1315/646/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized leachate treatment by using combination of struvite precipitation and coagulation-flocculation methods: RSM optimization

Abstract: Leachate is a form of pollution from landfills with pollutants in organic and inorganic forms. Stabilized leachate is characterized by the presence of organic materials with high ammoniacal nitrogen concentrations (>400mg/L), high chemical oxygen demand (COD) concentrations (<4000mg/L) and the ratio of BOD/COD is low (<0.1). In this study, struvite precipitation used to remove high ammonia content and coagulation-flocculation using poly-aluminium chloride (PAC) as coagulant agent and cationic polymer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Their application in leachate pretreatment has also been investigated, offering advantages such as cost-effectiveness, maneuverability, and stable and reliable treatment. Hurairah et al [29] utilized guano precipitation in conjunction with coagulation-flocculation to eliminate high levels of ammonia and COD, as well as to decolorize using polyaluminum chloride as a coagulant and cationic polymer as flocculants. The removal rates for COD, NH4 + -N, and color were 48.6%, 92.8%, and 98.8%, respectively.…”
Section: Coagulation-sedimentation and Air Flotation Technologymentioning
confidence: 99%
“…Their application in leachate pretreatment has also been investigated, offering advantages such as cost-effectiveness, maneuverability, and stable and reliable treatment. Hurairah et al [29] utilized guano precipitation in conjunction with coagulation-flocculation to eliminate high levels of ammonia and COD, as well as to decolorize using polyaluminum chloride as a coagulant and cationic polymer as flocculants. The removal rates for COD, NH4 + -N, and color were 48.6%, 92.8%, and 98.8%, respectively.…”
Section: Coagulation-sedimentation and Air Flotation Technologymentioning
confidence: 99%
“…16,17 The presence of nondiscrete dissolved organic matter (DOM) in LWE is known to hinder the struvite formation process, which is commonly carried out at optimal pH 9− 10. 18−22 Several approaches are known to mitigate these hindrances to struvite recovery from LWE through DOM removal from the dissolved phase by flocculation, 23,24 osmosis/ filtration, 25,26 and digestion. 27,28 In contrast to hindrance from non-descript DOM such as humic substances to struvite growth, 13,18,29 negatively charged low molecular weight (LMW) organics such as phenols and carboxylic acids promoted nucleation and growth of struvite in simulated LWE.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of nondiscrete dissolved organic matter (DOM) in LWE is known to hinder the struvite formation process, which is commonly carried out at optimal pH 9–10. Several approaches are known to mitigate these hindrances to struvite recovery from LWE through DOM removal from the dissolved phase by flocculation, , osmosis/filtration, , and digestion. , In contrast to hindrance from non-descript DOM such as humic substances to struvite growth, ,, negatively charged low molecular weight (LMW) organics such as phenols and carboxylic acids promoted nucleation and growth of struvite in simulated LWE. , Additional research found that adding a negatively charged soluble short peptide labeled shADP5 (short human-derived amelogenin-derived peptide 5, 1736.8 g mol –1 ) to simulated wastewater (SWW) also increased the struvite precipitation rate. This study evaluated the relationship between the ionic charge of the dissolved LMW organics benzylamine, benzoate, and toluene to struvite growth rates and morphology in SWW.…”
Section: Introductionmentioning
confidence: 99%
“…The aerobic, anaerobic, and/or anoxic biological processes are applied to eliminate ammonium and organic matter (Castrillón et al, 2010; Dahlan, 2019; El‐Gohary & Kamel, 2016; Mccarty, 2018). A large variety of physicochemical processes, for instance, activated carbon adsorption (Ghani et al, 2017; Reshadi et al, 2020), distillation or evaporation (Di Maria & Sisani, 2017), coagulation–flocculation–precipitation (Bouchareb et al, 2020; Hurairah et al, 2021; Kamaruddin et al, 2017; Tripathy & Kumar, 2019), chemical oxidation (Bouchareb et al, 2021; Jung et al, 2017; Mahtab et al, 2021), and membrane separation (Chan et al, 2007; Isik et al, 2021), have been engaged for leachate wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%